Influence of sustainable cutting environments on cutting forces, surface roughness and tool wear in turning of Inconel 718. (2018) - Mehta, A; Hemakumar, S.; Patil, A.; Khandke, S.P.; Kuppan, P.; Oyyaravelu, R.; Balan, A.S.S.
Abstract: Inconel 718 is a potential material for aerospace, nuclear and automobile industries because of its resistance to high temperature and corrosion. It becomes important to ensure good surface quality for better part performance and life. This paper shows a comparative study of the cutting forces, surface roughness and analysis of tool wear while machining of Inconel 718 under different sustainable machining environments such as dry, minimum quantity lubrication (MQL), cryogenic, cold air and MQL, MQL and cryogenic. The cutting speed, feed rate and depth of cut were kept constant for all environments based on the previous studies from literature. Results showed that machining using combination of cold air and MQL tends to reduce the surface roughness by about 86% and cutting force by about 28% when compared to dry machining. The minimum flank wear was obtained under MQL and cryogenic cutting condition (127.8µm) which is about 92% lower when compared to dry condition.